Mitral Valve Endocarditis with Perforation from a Urinary Source: An Unusual Case and Literature Review - Fernando Figueroa Rodriguez; Antonio Faieta Lasarcina; Francisco Davila Grijalva (Case Reports in Cardiology)
Aerococcus urinae (AU) is a rare pathogen, identified as gram-positive, catalase-negative coccus that grows in pairs and clusters which has been reported to mainly cause urinary tract infections (UTI), especially in elderly males. Treatment for this microorganism is usually with beta-lactams although cultures with antibiotic susceptibility testing are imperative. We present a case of AU endocarditis initially treated with IV antibiotics; nevertheless, the patient required emergent mitral valve replacement due to severe mitral insufficiency and perforation. We also present an analysis with high-yield points summarizing epidemiology, risk factors, microbiology, clinical features, diagnostic workup, and management of AU in general and AU endocarditis. Finally, we post a literature review of relevant cases and the impact of different variables associated with it.